PERHITUNGAN PAJAK PPH BADAN DAN PAJAK PERTAMBAHAN NILAI YANG ADA PADA UMKM TOKO KOPI X - Putri, Zsazsabila Natalia; Anisa, Hilda Try; Andrian, Willy; Silmi, Silmi; Mazelfi, Ihsani (Ensiklopedia of Journal, 2024)
This study aims to apply tax regulations in order to fulfill the obligations of Corporate Income Tax (PPh) and Value Added Tax (VAT) for UMKM. The calculation in this study is carried out in accordance with Law Number 7 of 2021 concerning Harmonization of Tax Regulations with a rate for Corporate Income Tax of 22% and for VAT of 11%. Data collection is done through interviews, observation, and document analysis. The results of this study are to help UMKM in terms of taxation so that UMKM can fulfill their obligations as taxpayers and the sustainability of UMKM in the future. Keywords: Corporate Income Tax, Value Added Tax, UMKM